Uma etnografia sobre o trabalho sexual masculino na cidade de São Paulo - Lima, João Paulo Cavalcante (2017)
The sex industry undoubtedly moves millions of dollars annually in Brazil and billions of dollars worldwide. In view of the various possibilities of business existing in the Brazilian sex industry, for this thesis, our study will be limited to male prostitution, in view of the fact that the taboo and the stigmas about it are still many, which makes this subject scarcely studied and completely neglected by the scientific researches carried out in our country. In addition, there is no research in the area of Organizational Studies in Brazil that deals with male sex work, what justifies the originality of this work. Thus, this research has as the objective to present how the male sex commerce in the city of São Paulo is organized, through male prostitutes' perception, and to identify what are the factors that impact on the professionals' performance. For this, a qualitative research with ethnographic inspiration was done, considering this part of the notion of the social construction of the world of the prostitutes' work. To collect empirical material, a collection of field survey data was utilized by the use multiple techniques, such as: semi-structured interview, direct observation and in-depth case analysis. In all, 30 interviews were conducted, with an average of 50-minute records, and 6 months of direct observation in places where male prostitution in the city of São Paulo takes place. After transcriptions, interviews were submitted to analysis with the help of software WEFT-QDA®. For the substantive theory elaboration, I´ve selected the application of the Grounded Theory as methodology. During the data analysis process, information was grouped into 4 categories and 33 subcategories. By analyzing the data, I have identified a central theory category, with which all others are related, which has been named 'Male Sex Work: A Social Fallacy of an Easy and Transient Life'. The main results of this research reveal that the way the male sex market is organized in the current society of São Paulo breaks with the conception of territoriality, since currently, sex workers can prospect their clients through physical and / or virtual spaces of prostitution, thus arising a new conception of the organization of sex work, which has been termed in this substantive theory as interactional environments for sexual purposes. Another important result is that the profile of professionals working in the field of male sex work has undergone major changes in the last decades, mainly due to the tools of information technology and communication, which have greatly stimulated the entry of more individuals into this market. It is also due to the emergence and popularization of drugs for the treatment of erectile dysfunction, which eventually increased the useful life of these professionals in the sex market. The substantive theory proposed here is provisional and contingent and reflects the interpretation of a particular researcher. It is thus hoped that it will broaden the field of studies in the area of Organizational Studies and encourage researchers to continue research on male sex work.